Development of Lectora Math-UDE Media UDE Problem Solving Model for Algebra Story Problems for Grade V Elementary School Students: Pengembangan Media Lectora Math-UDE Model Pemecahan Masalah UDE Untuk Soal Cerita Aljabar Siswa Kelas V SD - Raihani Afifah; Trimurtini (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
In the current era of disruption, rapid and massive changes require every individual to prepare themselves to face various challenges. Therefore, 21st century skills from 4C to 6C. One important skill is critical thinking, can be improved through solving mathematical problems. This study aims to develop, feasibility, and effectiveness of the Lectora Math-UDE media with the UDE problem-solving model. The subjects included teachers, fifth grade elementary students, media and material practitioners. The researcher used the RnD method with the ADDIE model. Data were collected through observation, interviews, questionnaires, and tests. The research instruments consisted of media and material expert validation, pretests and posttests, and teacher and student response questionnaires. The data analysis techniques used were qualitative and quantitative. The validation results showed that the media scored 94% from media experts and 86% from material experts, both in the "Very Feasible" category. The t-test results showed a significant difference between the pretest and posttest (sig 0.000), and the N-Gain test was 0.56 with the criteria of "Quite Effective". Thus, the Lectora Math-UDE learning media with the UDE problem-solving model is quite effective in improving the ability to solve algebraic story problems of fifth grade elementary school students.